Perlunya reformasi kebijakan pajak UMKM: Analisis krisis kepailitan UD pramono sebagai pengepul susu - Adam, Muhammad Haikal (Maliki Interdisciplinary Journal, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, but often face policy challenges that are not aligned with the real conditions of business. This study examines the case of UD Pramono, a milk collector MSME in Boyolali, Central Java, which faced the threat of bankruptcy due to a tax bill of Rp671 million from 2018. The blocking of accounts by the tax office caused operational paralysis and threatened the livelihood of around 1,300 partner farmers. This study aims to analyze the impact of the MSME Final Income Tax policy on businesses with low profit margins and assess the effectiveness of government and related institutions interventions in resolving tax disputes. Through a qualitative-descriptive approach based on case studies, it was found that tax policy inconsistencies and lack of assistance were the main factors in the problem. This research emphasizes the importance of more flexible and equitable MSME tax policy reform, as well as the need for cross-sector collaboration in providing tax education and mediation to MSME actors to prevent bankruptcy and maintain the sustainability of the local economy.